The Blessed Sacrament - Mumbai Archive Project Team (Jio Institute, 2024)
The Blessed Sacrament, consecrated on Maundy Thursday, is brought forward from its location for the Communion ceremony. The hosts are stored in a tabernacle, which is shrouded in a veil—a locked box where the Eucharist (consecrated communion hosts) is stored as part of the ‘reserved sacrament’ rite.